SINTESIS DAN KARAKTERISASI XRD BAHAN KERAMIK Ca0,95Ba0,05TiO3 MELALUI METODE KOPRESIPITASI - Anthon Toim; S. Suasmoro (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
SYNTHESIS AND CHARACTERIZATION XRD OF CERAMIK MATERIALS Ca0,95Ba0,05TiO3 BY COPRECIPITATION METHOD. Calsium Barium Titanate of ceramic materials (CaBaTiO3) has been synthesized by coprecipitation method. Synthesis of Ceramic materials CaBaTiO3 using TiCl4 raw materials, CaCl2.2H2O, BaCl2.2H2O, and H2C2O4 was supplied by E.Merk with level ‘reagent grade’. CaBaTiO3 powders calcined at temperature of 700ºC, 800ºC, and 900ºC for two hours.Calcination powder  CaBaTiO3 refers to the result of  Thermal analysis (DTA). CaBaTiO3 was formed at calcination temperature of 900ºC afterword pellets was made with a diameter of 10,662 mm, 2,844 mm thick, and then sintered at temperatur 1200 ºC,1300 ºC,and 1400 ºC for 4 hours. The samples were analized by X-ray diffraction to determine the phase after heat treatment and to determine the crystaline lattice. Phase identification after heat treatment know as ‘search matched’ was caried out by Philps X’pert HighScorePlus software, afterword crystal analysis using rietica software. The result of the analysis showed the ceramic materials CaBaTiO3 form a single phase at the sintering temperatur of 1400ºC perovskite structure with space group Pnma(62) and lattice parameter a = 5,30299 Å, b =5,46031 Å, and c = 7,60411Å. and powder CaBaTiO3 at calcination temperature of  900 ºC perovskite structure with space group Pbnm(62) and lattice parameter a = 5,39672 Å, b =5,44062 Å, and c = 7,64439 ÅKeyword:CaBaTiO3, Coprecipitation,X-ray diffraction.